The origin of evil: the detective-criminal-victim triad in O sorriso da hiena, by Gustavo Ávila - Souza, Joao Vitor de Paula [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2023)
The present article aims to analyze the destabilization of the classic detective genre in O sorriso da hiena, a contemporary Brazilian detective novel published by Gustavo avila in 2017, to highlight delineations of the characters that make up the expected configuration of the classic crime fiction triad: detective-criminal-victim. Thus, the theoretical framework consists of texts that discuss the detective genre, from its genesis to updates of this type of narrative, especially regarding the mentioned triad, such as Franca & Sasse (2016), Leidens (2019), Marques (2016), Massi (2011), Oliveira (2016), and Todorov (2006). Therefore, from the interpretative analysis of the excerpts from the novel, there are comments made to highlight how the characters of the narrative are described, and how they relate to each other throughout the novel, leading to their reconfiguration. The analyses indicate, therefore, that the elements that compose the classic crime fiction triad are not rigid or fixed categories, but rather elements that are very flexible and adaptable to different times, cultures, and narratives. Hence, a destabilization, even if partial, of the classic whodunit genre, is illustrated, considering that avila's work presents delineations and relationships among characters that can be described as innovative. In this sense, the research enables unexpected reflections that were not observed in classic works, which testifies to the inventiveness of the genre, always prone to some kind of evolution, both at the formal and thematic levels.
Keywords: Brazilian contemporary literature; crime fiction; Gustavo avila; classic crime fiction triad; destabilization of crime fiction